Alternative 3′ UTR polyadenylation is disrupted in the rNLS8 mouse model of ALS/FTLD - Randall J. Eck; Paul N. Valdmanis; Nicole F. Liachko; Brian C. Kraemer (Molecular Brain)
Abstract Recent research has highlighted widespread dysregulation of alternative polyadenylation in amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with TDP-43 pathology (FTLD-TDP). Here, we identify significant disruptions to 3` UTR polyadenylation in the ALS/FTLD-TDP mouse model rNLS8 that correlate with changes in gene expression and protein levels through the re-analysis of published RNA sequencing and proteomic data. A subset of these changes are shared with TDP-43 knock-down mice suggesting depletion of endogenous mouse TDP-43 is a contributor to polyadenylation dysfunction in rNLS8 mice. Some conservation exists between alternative polyadenylation in rNLS8 mice and human disease models including in disease relevant genes and biological pathways. Together, these findings support both TDP-43 loss and toxic gain-of-function phenotypes as contributors to the neurodegeneration in rNLS8 mice, nominating its continued utility as a preclinical model for investigating mechanisms of neurodegeneration in ALS/FTLD-TDP.